Science Education in the early years of Elementary Education through the Science Fair for Little Scientists (Research, Society and Development, 2020)
The study sought to investigate the contributions of a Science Fair, held at the Science Museum, on exhibiting students from the early years of elementary school. The evaluation of the Fair took place in two moments, in which the participation of each child during the scientific event was analyzed, considering their interaction with the visiting public, their skills during the presentation and the mastery of the theme presented. In the second stage, the Fair was analyzed from the perspective of the participating teachers, through the semi-structured interview. Their perceptions during the development of the works for the Fair were also investigated, as well as possible changes in students and in the classroom. 85 Children and 10 teachers participated in the Science Fair, where the presence of students in the process of literacy and special education was identified. 19 works were presented, categorized as experiments, games and models. The results showed the students' involvement in the different stages of the event: from the definition of the themes until the moment of presenting the work to the public. It can be inferred that, through the evaluation carried out, the Science Fair was relevant to the promotion of scientific education in children, which contributed to positive changes in the school environment, as well as a means of social inclusion.